Diabetes Type 2 And Dysautonomies: Prospective Study Over 5 Years About 300 Cases - AHMED ANAS, Dr GUEBOUB; HALIMA, Pr BENJELLOUN; YASSINE, Dr ERRAHALI; JAD, Dr ISSOUANI; SANAE, Dr CHAKDOUFI; SOUAD, Dr MOUSSAOUI; GHIZLAINE, Pr BELMEJDOUB (Journal of Medical Biomedical and Applied Sciences, 2018)
Rational - Diabetes is by far, the leading cause of vegetative neuropathy in the world. Dysautonomia is one of the major complications of diabetes, it is responsible for very diverse manifestations that can, in advanced forms, be responsible for major dysautonomia affecting several organs. Nevertheless, it has been suggested recently, that a sympathetic hyperactivity would be predictive of the onset of type 2 diabetes. Our goal was to examine the relationship between type 2 diabetes and dysautonomia.Patients and methods - This is a prospective descriptive study that took place over 5 years from June 2013 to June 2018, involving 300 non-hypertensive diabetic patients recruited at the endocrinology department of diabetology Mohammed V military hospital in Rabat.Results â The association between sympathetic hyperactivity and type 2 diabetes in non-hypertensives diabetics was confirmed in our study (pâ¤0.05). Male subjects were found to develop more sympathetic hyperactivity than female subjects (pâ¤0.05). Also, there was a significant correlation between vagal impairment and the age of diabetes (pâ¤0.05). Conclusion â The responsibility for sympathetic dysfunction in the genesis or aggravation of metabolic disorders is currently confirmed.